TCM-ADMEpred: A novel strategy for poly-pharmacokinetics prediction of traditional Chinese medicine based on single constituent pharmacokinetics, structural similarity, and mathematical modeling. (23rd May 2019) - Wang, Ping; Li, Ke; Tao, Ye; Li, Defeng; Zhang, Yi; Xu, Haiyu; Yang, Hongjun
Abstract: Ethnopharmacological relevance: Yuanhu Zhitong prescription (YZP) is a commonly used and relatively simple clinical herb preparation recorded in the China Pharmacopoeia. It contains Corydalis yanhusuo (Chinese name, Yanhusuo [YH]) and Angelica dahurica (Hoffm.) (Chinese name, Baizhi [BZ]), and has a long history of use in traditional Chinese medicine (TCM) for the treatment of stomach pain, hypochondriac pain, headache, and dysmenorrhea. Aim of the study: A TCM-ADMEpred method is developed for novel strategy for poly-pharmacokinetics prediction of TCM. To predict the pharmacokinetic characteristics of the main YZP constituents in rat plasma using in silico models, based on the theory that structurally similar constituents show similar pharmacokinetic properties. This approach may facilitate in silico prediction of the pharmacokinetics of TCM. Materials and methods: A robust platform using ultra-performance liquid chromatography coupled with triple quadrupole electrospray tandem mass spectrometry (UPLC-ESI-MS/MS) was developed and validated for simultaneous determination of seven active YZP constituents in rat plasma. These seven compounds were divided into two structural classes, alkaloids and coumarins. The correlation between AUC profiles within a structural class was expressed as Γ +, and this variable was used to develop two novel in silico models to predict constituent AUC values. The pharmacokinetics of tetrahydropalmatine, tetrahydroberberine, and corydaline following YZP administration were predicted using the Γ + -values of α-allocryptopine observed following YH administration, while those of imperatorin and isoimperatorin following BZ administration were predicted using the Γ + -values of byakangelicin observed following YZP administration. Results: The UPLC-ESI-MS/MS method was successfully used to evaluate pharmacokinetic parameters after oral YZP, YH, or BZ administration. Our findings showed that co-administration of YH and BZ increased the AUC of four alkaloid constituents and reduced the AUC of three coumarin constituents, which might provide a scientific rationale for co-administering these herbs clinically as a YZP preparation, thus increasing their efficacy and reducing toxicity. The AUC values of imperatorin and isoimperatorin were predicted 3 h after oral BZ administration, with the bias ratios between the theoretical values and the observed experimental values ranging from 0.61% to 11.4%, and average bias ratios of 5.8% and 8.0%, respectively. The AUC values of tetrahydropalmatine, tetrahydroberberine, and corydaline were predicted 3 h after oral YZP administration, with bias ratios ranging from 3.7% to 46.4%, and average bias ratios of 23.8%, 15.4%, and 25.8%, respectively. Conclusion: The UPLC-ESI-MS/MS method was successfully applied to pharmacokinetic evaluations after oral administration of YZP, YH, and BZ to rats. The Γ + variable was used to express the correlation between the AUC profiles of structurally similar compounds. This facilitated the development of an in silico model that was used to predict the AUC of three alkaloids in YZP and of two coumarins in BZ. Calculation of the bias ratios between the predicted and experimental values suggested that this in silico model provided a viable approach for the prediction of TCM pharmacokinetics. Graphical abstract: fx1